2021
DOI: 10.3389/fimmu.2021.679953
|View full text |Cite
|
Sign up to set email alerts
|

Current Challenges for IDO2 as Target in Cancer Immunotherapy

Abstract: Immune checkpoint inhibitors have revolutionized the clinical approach of untreatable tumors and brought a breath of fresh air in cancer immunotherapy. However, the therapeutic effects of these drugs only cover a minority of patients and alternative immunotherapeutic targets are required. Metabolism of l-tryptophan (Trp) via the kynurenine pathway represents an important immune checkpoint mechanism that controls adaptive immunity and dampens exaggerated inflammation. Indoleamine 2,3-dioxygenase 1 (IDO1), the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Three enzymes catalyze the rate-limiting step of the KP that transforms Trp into a series of biologically active metabolites: IDO1, IDO2 and TDO2 (Figure 1). Contrary to the uncertain role and regulation of IDO2, IDO1 and TDO2 are well-characterized intracellular heme-containing metalloproteins that are responsible for the degradation of the majority of Trp intake (19).…”
Section: Immunomodulatory Role Of the Trp Catabolism Pathwaymentioning
confidence: 99%
“…Three enzymes catalyze the rate-limiting step of the KP that transforms Trp into a series of biologically active metabolites: IDO1, IDO2 and TDO2 (Figure 1). Contrary to the uncertain role and regulation of IDO2, IDO1 and TDO2 are well-characterized intracellular heme-containing metalloproteins that are responsible for the degradation of the majority of Trp intake (19).…”
Section: Immunomodulatory Role Of the Trp Catabolism Pathwaymentioning
confidence: 99%
“…IHC results indicated that the IDO2 expression of lymph node tissues was signi cantly related to the metastasis status (P=0.002; Table 5). Previous studies have not reported such a remarkable effect of IDO2 on lymph node metastatic status (55), suggesting that IDO2 may play distinct roles based on the pathophysiologic feature or immune microenvironment of different cancers. Moreover, survival analysis suggests that high expression of IDO2 tends to result in a worse prognosis in patients with MTC.…”
Section: Disscussionmentioning
confidence: 91%
“…Although IDO2 can also initiate the Trp pathway, the affinity and catalytic efficacy of IDO2 for the substrate are very low [ 2 ]. Therefore, IDO2 may have little effect on the whole Trp metabolism [ 3 , 4 , 5 ]. The expression level of IDO1 closely correlates with poor prognosis of tumor, and IDO1 inhibitors have shown significantly limit tumor growth [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%